Workers of another world - "Heuze, Gerard" (Delhi, 1996)
Workers of Another World is a sociological study of the mining industry of Dhanbad, the centre of a coal belt situated 250 kilometres to the north-west of Calcutta. Some 50 million tonnes of the black diamond are carved out from the earth every year here by more than 200,000 miners who live with their families on the fringes of this old and fast-changing industrial region. The industry puzzles the workers even as it uses them. In order to examine the relationship between the workers and the industry the author studies the reaction of the miners to work, employment, and unemployment as well as the larger forces which dominate their lives. The present edition has been substantially revised from the French edition published in 1989 in the light of the more recent social changes which include the effects of mechanization in the mines, the changes in the economic policy, the rise of militant Hinduism, the evolution of a Jharkhandi cultural and organizational framework, and the changes in the political situation in the coal fields. Theoretical amendments deal with the family system, the different notions of self and identity, and the process of classification of social groups through state intervention.
Keywords: Coal mines - Dhanbad - Labour and labouring class